Perceptions experienced by nursing undergraduates in a tele-simulation scenario about neonatal hypoglycemia (Cogitare Enfermagem)
Objective: Describe perceptions experienced by nursing students in the tele-simulation scenario about neonatal hypoglycemia and expressed in self-assessment.